Influence of growth conditions on hydrophobicity of Lactobacillus acidophilus and Bifidobacterium lactis cells and characteristics by FT-IR spectra. Issue 3 (2010) - Shakirova, Laisana; Auzina, Lilija; Zikmanis, Peteris; Gavare, Marita; Grube, Mara
Abstract : In this study we have found, that the values of cell surface hydrophobicity (CSH) of L. acidophilus LA5 and B. lactis Bb12 cells change in response to varied growth conditions – phase of growth, concentration or type of carbon source, presence of oxygen. An evaluation of FT-IR spectra using cluster and quantitative analyses revealed substantial changes of the chemical composition depending on the CSH level of L. acidophilus LA5 and B. lactis Bb12 cells. Decrease of the carbohydrate level was observed in proportion to the increased CSH values alongside with the elevated protein content of more hydrophobic cells of both cultures. The results of present study could help to specify the appropriate physiological state and environment for L. acidophilus LA5 and B. lactis Bb12 to ensure their probiotic properties.